Scanning X‐ray microdiffraction of decellularized pericardium tissue at increasing glucose concentration. Issue 10 (4th July 2019) - Giannini, Cinzia; Terzi, Alberta; Fusaro, Luca; Sibillano, Teresa; Diaz, Ana; Ramella, Martina; Lutz‐Bueno, Viviane; Boccafoschi, Francesca; Bunk, Oliver
Abstract: Blood glucose supplies energy to cells and is critical for the human brain. Glycation of collagen, the nonenzymatic formation of glucose‐bridges, relates to diseases of aging populations and diabetics. This chemical reaction, together with its biomechanical effects, has been well studied employing animal models. However, the direct impact of glycation on collagen nano‐structure is largely overlooked, and there is a lack of ex vivo model systems. Here, we present the impact of glucose on collagen nanostructure in a model system based on abundantly available connective tissue of farm animals. By combining ex vivo small and wide‐angle X‐ray scattering (SAXS/WAXS) imaging, we characterize intra‐ and inter‐molecular parameters of collagen in decellularized bovine pericardium with picometer precision. We observe three distinct regimes according to glucose concentration. Such a study opens new avenues for inspecting the effects of diabetes mellitus on connective tissues and the influence of therapies on the resulting secondary disorders. Abstract : The direct effects of nonenzymatic glycation on the structure of collagen have been quantified in a new model system for the study of diabetes and age‐related effects.